An Study on Prevalence of Diarrhea Cases Caused by Salmonella in lambs in Hama Province (Journal of Hama University, 2020)
This study aimed to detect prevalence of diarrhea cases caused by Salmonella bacteria in these lambs in Hama governorate. The study was conducted on 300 stool samples of affected lambs with diarrhea in sheep flocks in in Hama governorate. The results of bacterial isolation and biochemical tests of salmonella species showed that 8 samples were positive cases of 300 samples of diarrheic lambs, with total prevalence of 2.67%. The upper prevalence of diarrhea cases caused by Salmonella in lambs was in Jargisa region as reported prevalence 8.33%, while prevalence of diarrhea cases caused by Salmonella in lambs was in areas Takses, Souran, Hamra and Bserin as 0.00% , These results reflect an important risk index on public veterinary health and public health.